Psychodynamic Aspects of Professional Resistance in Trauma Treatment - Mariia Tyshchenko (The Global Psychotherapist)
The article is devoted to the study of the phenomenon of psychotherapists' resistance in the work with psychotrauma, considered within the framework of the psychodynamic approach and positive psychotherapy. The author analyses the internal and external factors that cause resistance: secondary traumatisation, emotional burnout, unprocessed personal or transgenerational trauma, countertransference, stigmatisation of violence, religious beliefs, and ethical dilemmas. Particular attention is paid to the physical, emotional, and cognitive manifestations of resistance in the four spheres of the therapist's life. A five-stage model of self-help based on positive psychotherapy is proposed as a tool for overcoming professional disadaptation. The article proposes for discussion that the therapist's resistance is not a manifestation of incompetence, but rather a reflection of deep internal dynamics that can serve as a resource for growth. The practical significance of this work lies in creating a holistic conceptual framework for self-reflection, supervisory support, and the professional development of therapists working with trauma.